Análisis de la variabilidad de adn de cloroplastos en Quercus ilex L., Q. suber L. Y Q. coccifera L.. - COLLADA, C; Jimenez, P; Gil, L (III Congreso Forestal Español, 2001)
Chloroplast (Cp) and mitochondrial (mt) DNA variation have been studied by PCR-RFLP in 14 location (13 with Q. suber, 12 with Q. ilex and 6 with Q. coccifera) along the natural distribution area of these species in the Iberian Peninsula. Five chloroplast DNA primers pairs and one mitochondrial DNA primer pair have been used, each one in combination with a restriction enzyme. 29 different haplotypes have been detected, In the case of Q. suber a characteristic haplotype, very divergent of the remaining ones has been described. Usually, species don’t share haplotypes within the same populations. The distribution of haplotypes suggests a geographical structuring. The levels of genetic differentiation are similar to those obtained in oaks.hS is significantly higher in Q. ilex (hS=0,262). Differentiation coefficients (Gst) are similar in the three species and indicate a high typical structuring of maternal markers.
Keywords: chloroplast DNA; differentiation; geographic distribution; Haplotypes; phylogeny; Quercus